Characterization of the structural, thermal, mechanical and electrical properties of bacterial cellulose - Machado, João Manuel Martins (2010)
Although chemically similar to plant cellulose, bacterial cellulose (BC) produced by Gluconoacetobacter xylinum, a strict aerobe bacteria, is chemically pure, as is deprived of non-cellulosic polysaccharides (Jonas et al., 1998; Vandamme et al., 1998; Klemm et al., 2001; Amano, et al., 2005; Helenius et al., 2006). Its unique properties include high water holding capacity, high crystallinity, ultrafine fiber network, high tensile strength in the wet state, the ability to be shaped into 3D structures during synthesis (in-situ moldability) and excellent shape retention (Klemm et al., 2001; Helenius et al., 2006). The unique properties provided by the nanomeric structure of BC offer a wide range of applications such as in the human and veterinary medicine, odonthology, pharmaceutical industry, acoustic and filter membranes, biotechnological devices and in the food and paper industry. This work is focused on the production and characterization of bacterial cellulose from Gluconoacetobacter xylinus (ATCC 53582 and ATCC 10245 strains) concerning its structural, thermal, mechanical, electrical and morphological properties.